(untitled) (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Identità e alterità nello sport. Religioni, etiche e culture a confronto - 2. L’avvento della pluralità nel diritto sportivo e la (quasi) finita stagione della neutralità - 3. La discriminazione etnico-confessionale nella pratica sportiva. Gli strumenti normativi e istituzionali europei di contrasto alla condotta discriminatoria - 4. Quando il mondo dello sport arriva prima: la nascita del c.d. ius soli sportivo (legge 20 gennaio 2016 n. 12). Sport, religion and cultural pluralism: the multiple forms of contrast to the ethnic-confessional discrimination ABSTRACT: The article deals with the theme of recognizing and regulating identity and diversity in sport with a focus on religious element and the recent and gradual change of attitude of sports federations with respect to it, moving slowly from the time of secularity-neutrality in sport to the recognition of the athlete’s religious identity. The second part of the paper examines the theme of ethnic-confessional discrimination in sporting practice and analyzes the European normative and institutional instruments for contrasting discriminatory behavior and the prospects for this action coordination, also taking into account the birth of the “c.d. Ius soli sportivo” (Law 20 January 2016 No. 12) in Italy, a great innovation for a Country as ours still argues, at the level of citizenship, in a logic of “ius sanguinis”